2014
DOI: 10.1098/rspb.2014.0301
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional space: locomotory style explains memory differences in rats and hummingbirds

Abstract: While most animals live in a three-dimensional world, they move through it to different extents depending on their mode of locomotion: terrestrial animals move vertically less than do swimming and flying animals. As nearly everything we know about how animals learn and remember locations in space comes from two-dimensional experiments in the horizontal plane, here we determined whether the use of three-dimensional space by a terrestrial and a flying animal was correlated with memory for a rewarded location. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 27 publications
0
27
0
1
Order By: Relevance
“…If one is interested in whether an animal can use certain types of information, for example, then even in the laboratory there are already a variety of testing paradigms. For instance, to determine which cues an animal uses to return to a location, there is often a convergence on standardized paradigms, such as the radial maze or the Morris Water Maze, although these devices can come in different forms (e.g., Bond, Cook & Lamb, ; Flores‐Abreu, Hurly, Ainge, & Healy, ; Hilton & Krebs, ; Spetch & Edwards, ). In the wild, in order to ensure an animal's participation, these paradigms, at least in their laboratory form, may well be unsuitable, forcing field experimenters to “think outside of the box.” As the variety in the laboratory suggests, conformity to established paradigms need not be strictly enforced, and novel experimental designs can be used to address familiar questions.…”
Section: Why Study Cognition In the Wild?mentioning
confidence: 99%
“…If one is interested in whether an animal can use certain types of information, for example, then even in the laboratory there are already a variety of testing paradigms. For instance, to determine which cues an animal uses to return to a location, there is often a convergence on standardized paradigms, such as the radial maze or the Morris Water Maze, although these devices can come in different forms (e.g., Bond, Cook & Lamb, ; Flores‐Abreu, Hurly, Ainge, & Healy, ; Hilton & Krebs, ; Spetch & Edwards, ). In the wild, in order to ensure an animal's participation, these paradigms, at least in their laboratory form, may well be unsuitable, forcing field experimenters to “think outside of the box.” As the variety in the laboratory suggests, conformity to established paradigms need not be strictly enforced, and novel experimental designs can be used to address familiar questions.…”
Section: Why Study Cognition In the Wild?mentioning
confidence: 99%
“…Indeed, 3D-moving species acquire spatial information in the vertical plane with a similar or higher accuracy than information in the horizontal plane, whereas surface-bound species are less accurate in the vertical space (Dacke and Srinivasan, 2007;Eckles et al, 2012;Flores-Abreu et al, 2014;Holbrook and Burt de Perera, 2013;Hurly et al, 2010). However, locomotory style does not predict the relative importance of horizontal and vertical information to an animal: vertical information is preferred in fish (both benthic and non-benthic organisms) but not in hummingbirds, two equally 3D-moving species.…”
Section: Introductionmentioning
confidence: 99%
“…An animal's mode of locomotion is likely to influence how threedimensional information is encoded in its brain (Flores-Abreu et al, 2014). Indeed, 3D-moving species acquire spatial information in the vertical plane with a similar or higher accuracy than information in the horizontal plane, whereas surface-bound species are less accurate in the vertical space (Dacke and Srinivasan, 2007;Eckles et al, 2012;Flores-Abreu et al, 2014;Holbrook and Burt de Perera, 2013;Hurly et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the locomotor style of an animal is correlated with the accuracy with which spatial information in the horizontal and vertical planes is encoded and which of this information is prioritized (Flores-Abreu et al, 2014). Animals able to move freely in the three dimensions (e.g., fish, bats, bees, birds) encode the vertical information with either equal or higher accuracy than the horizontal information and seem to prefer vertical to horizontal information, while animals constrained to a surface (e.g., rats) do the opposite (Hurly et al, 2010; Holbrook and Burt de Perera, 2013; Davis et al, 2014; Flores-Abreu et al, 2014; but see Ulanovsky, 2011; Savelli and Knierim, 2013; Yartsev and Ulanovsky, 2013; Scatà et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Animals able to move freely in the three dimensions (e.g., fish, bats, bees, birds) encode the vertical information with either equal or higher accuracy than the horizontal information and seem to prefer vertical to horizontal information, while animals constrained to a surface (e.g., rats) do the opposite (Hurly et al, 2010; Holbrook and Burt de Perera, 2013; Davis et al, 2014; Flores-Abreu et al, 2014; but see Ulanovsky, 2011; Savelli and Knierim, 2013; Yartsev and Ulanovsky, 2013; Scatà et al, 2016). However, species of bees that differ in their use of vertical space also differ in the accuracy with which they learn height and in their ability to communicate this information (Nieh et al, 2003; Dacke and Srinivasan, 2007; Eckles et al, 2012).…”
Section: Introductionmentioning
confidence: 99%